Implementation of 21st Century 6C Skills in Learning to Write Literature through Novel Adaptation Approach - Jupri, Abdul Rahman; Solihati, Nani; Sari, Zamah (Indonesian Journal of EFL and Linguistics, 2024)
Learning to write literature in higher education needs to prioritize creative learning so that students can feel the benefits of literary learning in honing 6C skills by the character of 21st-century learning. This research aims to describe the implementation of 21st-century 6C skills in learning to write literature in higher education through an adaptation novel approach. This research is art-based qualitative research. Observation and interview methods were used to obtain research data. The research was conducted on 80 students at Muhammadiyah University, Prof. DR Hamka, consisting of 68 women and 12 men. Data analysis was carried out using qualitative descriptive methods. Meanwhile, the validity of the data is carried out by theoretical triangulation. Theoretical triangulation in this research was carried out by examining the data obtained with theories originating from expert opinions or previously existing theories. The results of this research illustrate that the 6C skills of 21st-century learning (Critical thinking, Communication, Collaborative, and Creative skills, culture, and Connectivity) can be implemented in learning to write literature. Apart from that, the novel adaptation approach can help students improve their abilities in writing literature.